Mainstreaming Conservative Ideas Through Media Coverage - Anamaria Hanžek (Politikon)
This study examines how Croatian online media coverage of the “Be Manly” men’s rights movement contributed to mainstreaming conservative ideas. “Be Manly” emerged in 2022 as a Catholic men’s movement conducting public prayer protests to advocate for male authority and traditional gender roles. Using critical discourse analysis, this research analyzed 72 articles from five major online news outlets (Index.hr, Jutarnji.hr, 24sata.hr, Večernji.hr, and Dnevno.hr) during the movement's first year. The findings reveal an ideological divide: Index.hr and Jutarnji.hr demonstrated negative coverage, while 24sata.hr, Večernji.hr, and Dnevno.hr portrayed the movement positively. However, all outlets participated in mainstreaming conservative ideas through three mechanisms: temporal-spatial normalization, agenda setting, and trivialization. This study provides the first systematic analysis of media representation of men’s rights activism in Croatia, revealing how ideological bias in media coverage can facilitate the mainstreaming of conservative ideas.